Seasonal variation of ecosystem photosynthetic capacity and its environmental drivers in global grasslands - Chen, Xiuzhi; Ren, Xiaoli; He, Honglin; Zhang, Li; Lv, Yan (Frontiers in Ecology and Evolution, 2023)
Ecosystem maximum photosynthetic rate (Amax) is an important ecosystem functional property, as it is critical for ecosystem productivity modeling. However, little is known about the mechanisms that regulate the seasonal variation of Amax in grasslands, one of the dominant vegetation types worldwide. In this study, we analyzed the seasonal variability of Amax of grassland sites across the globe and its environmental drivers. We found that grassland Amax had strong seasonal variations, which were influenced by the climate and agricultural management, such as grass cutting and grazing. Second, the seasonal variation of Amax at all arid grasslands [mean annual vapor pressure deficit (VPD) > 10 hPa] was driven more by changes in canopy physiological property (i.e., maximum photosynthetic rate per leaf area Amaxa) than canopy structural property (i.e., leaf area, presented by LAI), because Amaxa had stronger temporal variability than LAI in these ecosystems. Third, temperature and VPD were the most influential factors for the seasonal variability of Amax and LAI, but environmental variables only explained a small proportion of the seasonal variation of Amaxa, which was probably because Amaxa was more related to plant traits. Our findings provide new ideas for better parameterizations of Amax in terrestrial ecosystem models.